IN VIVO ASSESSMENT OF GROWTH PROMOTING ACTIVITY OF A SYNTHETIC B-FGF IN WOUND HEALING OF RAT’S SKIN - Bazzaz, Ayoub A; Bukhari, Fatin O; Bazzaz, Zumrud A; Chelebi, Noorhan A (European Scientific Journal, ESJ, 2014)
A single 0.3μg/mL of synthetic b-FGF topical dose was applied in vivo on a model of freshly made twin scalp wounds of 8 mm length in full dermal thickness skin of 20 male albino rats Rattus norvegicus under anesthesia, while an adjacent wound was washed only with phosphate buffer saline (PBS) as an untreated or control. The rats at different times i.e. 15 minutes-10 days were then dissected under anesthesia and perfused with 10% formalin fixative in PB in 0.1M PB of pH7.4 through the left ventricle. Skin samples of both wounds were then processed using routine histology technique and stained with Heamatoxylen and Eosin (H&E) as well as for antibodies raised against substance-P. The morphological observations showed a significantly early closure (50% time scale) of the wounds topically treated with b-FGF at day two in comparison with those of controls of the same individual animals. Histological results had confirmed the potency of the 0.3 ng/mL dose of b-FGF in inducing a rapid, almost in half healing time via re-epithelialization, a rapid maturation of newly formed fibers, angiogenesis, contraction and significantly accelerated the wound closure time of treated rats to almost half time in comparison with controls. The single low dose topical application of b-FGF had accelerated the proliferation process of skin tissue components confirming its curing potency for both pharmaceutical industry and in medicine in curing skin wounds.